1986
DOI: 10.1111/j.1528-1157.1986.tb03606.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement of Children with Epilepsy

Abstract: The academic achievement scores of 122 children with epilepsy were examined in relation to demographic and clinical seizure variables. As a group, these children were making less academic progress than expected for their age and IQ level. Academic deficiencies were greatest in arithmetic, followed by spelling, reading, comprehension, and word recognition. Results of the multiple regression analyses indicated a modest combined predictive significance of the demographic and clinical seizure variables for academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
109
4
9

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(141 citation statements)
references
References 23 publications
(8 reference statements)
19
109
4
9
Order By: Relevance
“…Intractable epilepsy in children with onset before age two has been associated with poor cognitive functioning (38). Moreover, in the sample of children with new-onset seizures, our finding that academic performance among those with recurrent seizures tended to decline over time is consistent with results from previous research (7,8,10,32), emphasizing the importance of identifying academic difficulties among children with seizures as early as possible so that interventions may be implemented that limit the progression of problems. This finding is even more important in light of the fact that our sample included only children with normal development and they were starting to show decline over time.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Intractable epilepsy in children with onset before age two has been associated with poor cognitive functioning (38). Moreover, in the sample of children with new-onset seizures, our finding that academic performance among those with recurrent seizures tended to decline over time is consistent with results from previous research (7,8,10,32), emphasizing the importance of identifying academic difficulties among children with seizures as early as possible so that interventions may be implemented that limit the progression of problems. This finding is even more important in light of the fact that our sample included only children with normal development and they were starting to show decline over time.…”
Section: Discussionsupporting
confidence: 89%
“…Although some early studies reported higher academic achievement for females than for males with epilepsy (16-18), others found no main effect for gender (7,19). In a recent study, Austin and colleagues (10) found males with high severity epilepsy to have the most risk for underachievement.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations